Indoor air pollution from cookstove smoke and adverse health effects among Honduran women - Clark, Maggie L., author; Peel, Jennifer, advisor (Colorado State University. Libraries, 2007)
Elevated indoor air pollution exposures associated with the burning of biomass fuels in developing countries are well established. Several studies have demonstrated the value of estimating exposures by evaluating stove type, personal cooking practices, and household parameters. Adverse health endpoints have been associated with cookstove exposures, although little research has been performed on cardiovascular health endpoints in these settings. We conducted a cross-sectional survey among 79 non-smoking Honduran women. Thirty-eight women cooked with traditional stoves and 41 with improved stoves with chimneys. For a subgroup of these women (N=54-58), carbon monoxide and particulate matter (PM2.5) levels were assessed via eight-hour indoor monitoring, as well as eight-hour personal PM2.5 monitoring. Stove quality was assessed using a four-level subjective scale representing the potential for indoor emissions. The stove scale and ventilation factors predicted more than 50% of the variation in personal and indoor PM2.5 and 85% of the variation in indoor carbon monoxide. In addition to the stove scale, other factors predicting exposure measurements were the age of the stove, the total area of the kitchen windows, the number of kitchen walls, the primary material of the kitchen walls, the volume of the kitchen, and the number of walls with eave spaces. Forced expiratory volume in one second and peak expiratory flow, as well as respiratory symptoms and demographic characteristics were assessed. Finger-stick blood samples were collected and dried on filter paper in order to assess a biomarker of inflammation, C-reactive protein (CRP). Women exposed to cookstove exposures reported symptoms of cough, phlegm, wheeze, headache, and shortness of breath more frequently than those not exposed. Associations consistent with a null association were observed between cookstove exposures and lung function and CRP. Results of the exposure assessment could provide a cost-effective alternative to air quality monitoring. The ease and convenience of collecting, storing, and transporting finger-stick blood samples, could prove to be a useful tool for larger community-based investigations, especially in developing countries.
Keywords: air pollution; cookstove smoke; health effects; Honduras; indoor air; women; public health; epidemiology; indoor air quality; pollution studies; smoke inhalation; women